Public Labeling of Adolescents of Former Drug Convicts - Rahmi, Suhai Ratu; Erianjoni, Erianjoni (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2022)
This research is motivated by the large number of data found on drug convicts with juvenile offenders in the Class IIB Padang state detention center from Koto Tangah District which always changes every period. With these changes, it is evident that many of the juvenile convicts with repeated criminal acts, and have just been sentenced to detention in the Padang Class IIB State Detention Center. However, the freedom of the juvenile ex-convicts of drug cases makes it difficult for them to adapt, and get labels from society. This labeling aims to analyze the label of society towards adolescent ex-convicts of drug cases, and the impact of the label on the behavior of adolescent ex-convicts of drug cases. This study uses the theory of labeling and George Herbert Mead's socialization theory. The approach used is qualitative with the type of case study research. Research informants were determined using a purposive sampling technique with criteria for subsidy services for prisoners at the Padang Class IIB State Detention Center, juvenile ex-convicts in drug cases with the age of 12-21 years, families of juvenile ex-convicts in drug cases, and the community around the residence of juvenile ex-convicts. drugs. Data was collected using observation, interviews, and documentation studies. The data validity test includes credibility, transferability, dependability, and conformability tests. Analysis of the data using the interactive analysis model of Miles and Huberman. The results of the study show that the labeling of society on juvenile ex-convicts of drug cases is divided into two forms; First, the labeling of names (makaw, lelek, sakaw, maele, meang, and paisok). Second, the labeling of people's attitudes (parusuah, sampah masyarakaik, and pakak badak). Community labeling has an impact on the behavior of adolescent ex-convicts of drug cases, such as feelings of fear to adapt, repeat drug use, and uncontrolled emotions.